LIFEGUARD proteins support plant colonization by biotrophic powdery mildew fungi - Weis, Corina (Oxford University Press, 2013)
Pathogenic microbes manipulate eukaryotic cells during invasion and target plant proteins to achieve host susceptibility. BAX INHIBITOR-1 (BI-1) is an endoplasmic reticulum-resident cell death suppressor in plants and animals and is required for full susceptibility of barley to the barley powdery mildew fungus Blumeria graminis f.sp. hordei. LIFEGUARD (LFG) proteins resemble BI-1 proteins in terms of predicted membrane topology and cell-death-inhibiting function in metazoans, but display clear sequence-specific distinctions. This work shows that barley (Hordeum vulgare L.) and Arabidopsis thaliana genomes harbour five LFG genes, HvLFGa–HvLFGe and AtLFG1–AtLFG5, whose functions are largely uncharacterized. As observed for HvBI-1, single-cell overexpression of HvLFGa supports penetration success of B. graminis f.sp. hordei into barley epidermal cells, while transient-induced gene silencing restricts it. In penetrated barley epidermal cells, a green fluorescent protein-tagged HvLFGa protein accumulates at the site of fungal entry, around fungal haustoria and in endosomal or vacuolar membranes. The data further suggest a role of LFG proteins in plant–powdery mildew interactions in both monocot and dicot plants, because stable overexpression or knockdown of AtLFG1 or AtLFG2 also support or delay development of the powdery mildew fungus Erysiphe cruciferarum on the respective Arabidopsis mutants. Together, this work has identified new modulators of plant–powdery mildew interactions, and the data further support functional similarities between BI-1 and LFG proteins beyond cell death regulation.